If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -29 + -2x = 3x + 41 Reorder the terms: -29 + -2x = 41 + 3x Solving -29 + -2x = 41 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -29 + -2x + -3x = 41 + 3x + -3x Combine like terms: -2x + -3x = -5x -29 + -5x = 41 + 3x + -3x Combine like terms: 3x + -3x = 0 -29 + -5x = 41 + 0 -29 + -5x = 41 Add '29' to each side of the equation. -29 + 29 + -5x = 41 + 29 Combine like terms: -29 + 29 = 0 0 + -5x = 41 + 29 -5x = 41 + 29 Combine like terms: 41 + 29 = 70 -5x = 70 Divide each side by '-5'. x = -14 Simplifying x = -14
| -12-x=-5x+24 | | 5s+7s=-72 | | -12x=-5x+24 | | 3y+2.5=6(2-y) | | -8x=-63*(-1) | | -49-x=29-7x | | 9x-62=-2x+59 | | 2=11+(39m+3) | | -x-31=-8x+39 | | 2=11+39m+3 | | -x-31=8x+39 | | -75+6X=-4X+115 | | y=sin(e^5x) | | -75x+6x=-4x+115 | | 9x-9=-2x+46 | | 260=(3x+5)(3x-2) | | -75+6x=-4x+15 | | 3(5-x)+3=6(8+2x) | | 3x^2+8=76 | | 2(-x+8)=5(x+2)-2 | | 16-2x=-3(x-4) | | 1.45=1+3x+3x^2+3x^3+2x^4 | | 1.45=1+3x+3x^2+3x^3 | | 1.45=1+3x+3x^2 | | 1.45=1+3x | | -34+x=14-3x | | ln(5x)-ln(5)= | | 3x-92=68-7x | | 8(9y-2)-(6y+5)= | | z^2+(2i-3)*z+5-i=0 | | ln(3x+14)+ln(8)=2ln(x) | | 63=3(k+3)+2(k-3) |